Community Empowerment Towards a Clean Environment in Kembang Kuning Tourism Village, Indonesia - Linta Aulia; Ria Indriani; Asara Putri Nadiwa; Lolita Adinintiyas Putri; Lalu Kusumawardi; M. Zainul Kholil; Ahmad Yasar Ramdan (Tinta Emas Institute, 2025)
Kembang Kuning Tourism Village is located in Sikur District, Lombok Timur Regency, West Nusa Tenggara Province. This village is one of the tourist destinations famous for its natural beauty, such as mountain scenery, and unique local cultural wealth. These attractions make Kembang Kuning Village visited by many tourists every year. However, the increasing number of tourists brings its own challenges in maintaining the cleanliness and sustainability of the village environment. As a tourist destination, a clean and well-maintained environment is essential to maintain the village's image and attractiveness. Therefore, community empowerment efforts in maintaining environmental cleanliness are a top priority to support the sustainability of the village as an environmentally friendly tourist destination. Various community empowerment strategies have been carried out to increase residents' awareness and involvement in maintaining village cleanliness. The programs implemented include waste management training, the establishment of waste banks, and cleanliness campaigns involving the entire village community. This study aims to identify the effectiveness of community empowerment strategies that have been implemented in Kembang Kuning Village, evaluate the extent of community participation in cleaning activities, and analyze the impact of these programs on the quality of the village environment, as well as to provide recommendations to overcome obstacles faced, such as limited waste management facilities, minimal use of recycling technology, and lack of support from external parties. With better collaboration between the community, government, and tourism managers, Kembang Kuning Tourism Village can maintain the cleanliness and beauty of its environment in a sustainable manner.